Contamination of fresh produce sold on the Italian market with Cyclospora cayetanensis and Echinococcus multilocularis. (September 2021) - Barlaam, Alessandra; Temesgen, Tamirat T.; Tysnes, Kristoffer R.; Rinaldi, Laura; Ferrari, Nicola; Sannella, Anna R.; Normanno, Giovanni; Cacciò, Simone M.; Robertson, Lucy J.; Giangaspero, Annunziata
Abstract: To investigate the presence of Cyclospora cayetanensis, Toxoplasma gondii and Echinococcus spp. in fresh produce sold in Italy, 324 locally produced 'ready-to-eat' (RTE) mixed-salad packages belonging to three brands and 324 berries packages (blueberries and blackberries imported from Peru and Mexico, respectively, and raspberries grown in Italy) were purchased at retail. Nine individual packages from each of the six types of fresh produce were collected monthly for one year, and with the same produce pooled, this resulted in a total of 72 pools for the whole year. Using microscopy (FLOTAC), a Cyclospora -like oocyst was detected in a blueberry sample and a taeniid egg was detected in a RTE-salad sample. Molecular tools confirmed these to be C. cayetanensis and Echinococcus multilocularis, respectively. Toxoplasma gondii was not detected in any of the samples. This study shows for the first time in Europe that imported berries on the Italian market may be contaminated with C. cayetanensis and RTE salads grown in Italy with E. multilocularis . The results indicate a new epidemiological scenario and highlight that current management of fresh produce, locally produced or imported, does not ensure products are free from parasite contamination. Highlights: Fresh produce sold in Italy was investigated for contamination with three parasites. Microscopy and molecular tools were employed for detecting contamination. Cyclospora was detected in berries and Echinococcus multilocularis in RTE salad. Risk management for controlling parasites in fresh produce should be implemented.